Óptima coordinación de protecciones en alimentadores con generación distribuida para maximizar la confiabilidad mediante MINLP - Zapata Verdezoto, José Damián (2018)
The article refers to the optimal protection coordination on distribution systems, due to the fact that, normally on these systems there is an increase in short-circuit currents resulting in the delay of protection coordination and decreasing selectivity. A power flow will be simulated in the electrical system of 33 nodes of the IEEE, to determine the electrical variables associated with the quality of the product. The methodology also considers the application of a Mixed Integer Nonlinear Programming Model (MINLP), for the solution of power flows, which will include binary variables that decide the implementation of distributed generation (DG) in the nodes of the electrical system. The solution is performed using GAMS as optimizer, considering as an objective function the minimization of active losses and thus increase the reliability to the implementation of DG. As a result of this optimization, coordination of protections will be made to improve the electrical system considering the DG.